ADOPSI DAN PEMELIHARAAN ANAK DALAM HUKUM ISLAM - MS, Syaifullah; Datumula, Sarfika (Musawa: Journal for Gender Studies, 2021)
Adoption of children is one of the noble ways for couples who have not been blessed with children. The presence of an adopted child is expected to fill the lonely days of husband and wife, even sometimes many couples make their adopted children as a "lure" so that later they will have their own child. In Islamic law, in principle, an adopted child is not prohibited as long as it involves nurturing, educating and caring for him/her, however, the adopted child is not considered to become the heir or obtain inheritance if it is connected or associated with his/her legal position in Islamic law. Child is a person who must be protected from everything that can make it difficult for him/her, to be able to provide a good deed done by his/her parents, and with Hadhanah (the right to custody of a child under Sharia Law), it is very important that this Hadhanah is handed over to the mother because it is a job that requires a lot of responsibility and persistence in doing so.